2006
DOI: 10.1606/1044-3894.3537
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Workers’ Responses to Domestic Violence Cases: The Effects of Training and Worker Characteristics

Abstract: This study evaluated a one-day domestic violence training for Temporary Assistance for Needy Families (TANF) workers and analyzed the relationship between worker characteristics and the use of work exemptions. In a post-only evaluation, trained workers reported a greater tendency than untrained workers to refer clients to couples counseling, make a safety plan, and file a report to child protection services. In a pre/post evaluation, workers reported after training that they would be less likely to refer clien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…One study maintains that 54 percent of TANF recipients are in need of services addressing domestic violence (41), while another finds only 9 percent of TANF recipients are actually screened for domestic violence (42). Not surprisingly, those screened by appropriately trained workers are likelier to be referred for domestic violence services than those screened by untrained workers (43).…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…One study maintains that 54 percent of TANF recipients are in need of services addressing domestic violence (41), while another finds only 9 percent of TANF recipients are actually screened for domestic violence (42). Not surprisingly, those screened by appropriately trained workers are likelier to be referred for domestic violence services than those screened by untrained workers (43).…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…The relationship between treatment seeking for IPV and participation in welfare remains unexplored. However, TANF programs do feature a “Family Violence Option” under which work stipulations are waived for IPV victims (Pyles, 2006; Seefeldt & Orzol, 2005); through this opportunity, trained TANF staff help victims develop safety plans and refer them for other services (Saunders, Holter, Pahl, & Tolman, 2006). But only 9% of TANF recipients are screened for IPV (Lindhorst, Meyers, & Casey, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the studies included, MHPs included MFTs, social workers, counselors, psychologists, IPV service providers, substance abuse counselors, welfare managers, social work students, and family and marriage therapy students. Five themes were identified including lack of preparation and inadequate training in DV (Dersch et al, 2006;Fedina et al, 2017;Karakurt et al, 2013;Kress et al, 2008;Murray et al, 2015;Raphael-Dudley et al, 2008;Schneider, 2018;Todahl et al, 2008), benefits of DV training (Forgey et al, 2013;Kulkarni et al, 2015;McCloskey & Grigsby, 2005;Payne et al, 2007;Saunders et al, 2006), need for collaboration between service providers (Capezza et al, 2014;Macy & Goodbourn, 2012;Macy et al, 2009), stigmatizing attitudes and behaviors toward survivors (Crowe & Murray, 2015), and the advocate-survivor connection (Bogat et al, 2013;Wood, 2017). These studies can be found in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Mental Health Professionals and Domestic Violence (DV) Training.From this review, we found that formal DV training revealed a plethora of benefits. Multiple authors found that MHPs who received DV training were more prepared to work with survivors and showed improvement in their ability to administer assessments and safety plans(McCloskey & Grigsby, 2005;Saunders et al, 2006). Additionally, agencies with DV training and policies embedded into their organization were more likely to have MHPs participate in those trainings suggesting that organizational support increased participation…”
mentioning
confidence: 99%